THE INFLUENCE OF PRICES, PRODUCTS AND DISTRIBUTION ON RUBBER VINNEGAR PURCHASE DECISIONS AT UD. BULAN BINTANG RANAH AIR TIRIS VILLAGE - Khairul Basar; Zulher Zulher; Azhari Azhari (Jurnal Riset Manajemen Indonesia, 2021)
This research was conducted at UD. Bulan Bintang, which is located at Ranah Air Tiris Village, Kampar Regency, starts from March 2020 to completion. The type of data used consists of primary data and secondary data with a sample size of 50 people. The sample was conducted by using the census method. Meanwhile, to determine the magnitude of the independent effect (X) on the dependent variable (Y), Multiple Linear Regression analysis is used with the help of SPSS version 16.0. From the results of the normality test using the one sample Kolmogorovesmirnove test, the significance results of the normality test were 0.351, where the results were greater than the 0.05 significance level, so it can be concluded that the test tests on the normality test in this study were normally distributed. The Heteroscedasticity test shows that the dots are not randomly spread, and form a certain pattern, and are spread over the zero on the Y axis. So, it can be concluded that the regression model in this study is free from heteroscedasticity. The independent variable does not have a significant effect on the dependent variable. This can be seen based on the results of the t test and f test, where the significance value is 0.451> the α value is 0.05, this indicates that the hypothesis test is not significant.